(untitled) (Experimental biology, 2015)
In the present review, the authors consider the problem of the influence of psycho-emotional stress on the functional state of the human body, in particular, the possibility of stress-induced reproductive disorders and complications of gestational period in women. The review a historical excursion problems is affected, special attention is paid to modern concepts of physiological mechanisms regulating reactivity of women during gestation and lactation periods on the nature of the psychological and emotional stressors. Published data of endocrine regulation and possible dysfunctions of the reproductive sphere under stress are considered. It also analyzes the material for the development of oxidative stress, which is the basis of oxidative damage of membrane structures of erythrocytes, cells of mammary gland, as a result leads to the development of fetal abnormalities, miscarriage, low birth weight offspring, disruption of lactation and development hypogalactia.